PLANNING OF PRIVATE GATED DEVELOPMENT: AN ANALYSIS OF GATED VS NON-GATED NEIGHBOURHOODS, CITY OF GURUGRAM, INDIA - Kaushik, Ajay (PLANNING MALAYSIA, 2019)
The cities are expanding rapidly all over the world. India has also experienced this phenomenon and has continued the pace of growth. The recent trends in spatial growth of the cities are a new phenomenon in Indian urban landscape. The cities in India are witnessing development with the help of private developers for the last couple of decades. Being private properties these are by nature of exercising control have gates and boundaries. In scholarly literature these are called as Gated Community/Gated Development. Authors have argued them from various perspectives of anthropology, law, management and sociology etc. but very little has been discussed about their planning and morphology. Although, the rise of Gated Development is majorly attributed to the sense of fear and need for security, yet architects and urban designers, and even sociologist stress upon other methods to make the neighbourhoods secured. Hence the security aspects are not made part of the research here. The aspects of how these gated development impacts the perception of neighbourhood by residents is not touched upon. The paper discusses the distinction between the gated and non-gated neighbourhoods and also how residents perceive their neighbourhoods at large. For explaining this phenomenon, three neighbourhoods in the city of Gurugram in Haryana state in India have been identified as case study. These are identified on the basis of different morphological images that are identified. Space syntax and space cognition through sketch mapping is used for the analysis of the three neighbourhoods. The paper suggest that the continuity and connectivity of any spatial configuration is of utmost importance to make neighbourhood environment worthy of living life more socially connected.